Kingdom of Lesotho : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Kingdom of Lesotho. (IMF Staff Country Reports; Country Report ;, 2022)
Lesotho has been simultaneously hit by the pandemic, declining transfers from the Southern African Customs Union (SACU), and the impact of the war in Ukraine. The pandemic exacerbated the impact of sluggish regional performance, climate shocks, and longstanding structural issues such as regulation, governance, political stability, financial inclusion, and diversification. Public expenditure has continued to increase, such that the decline in external transfers precipitated significant financing pressures and growing domestic arrears. With limited inflows to the private sector, the resulting public sector-driven external imbalances have continued to put pressure on international reserves needed to maintain the exchange rate peg.